Determinants of Stock Prices: The Role of Company Size As A Moderating Variable - Yovita Kusuma Wardhani; Nina Dwi Setyaningsih (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
The purpose of this research is to investigate how the relationship between company size, which moderates the effect of financial performance, dividend policy, and corporate social responsibility (CSR), on stock prices. This research uses quantitative methods with causality approaches. Companies in the food and beverage subsector listed on the Indonesia Stock Exchange between 2019 and 2023 constitute the population. Sixty observational data points were collected from twelve companies that met the research objectives through a purposive sampling technique. Panel Data Regression and Moderated Regression Analysis were applied to analyze the hypotheses. The results of this study show that financial performance has a positive impact on stock prices. Meanwhile, dividend policy and corporate social responsibility have no impact on stock prices. Furthermore, company size does not moderate the impact of financial performance, dividend policy, and corporate social responsibility on stock prices.  This study supports the signaling theory that firms send signals to the market (investors) through financial performance reports and investors respond to these signals as markers of the company’s worth and prospects, so stock prices reflect this.